Prevalence of oral lesions and chronic non-communicable diseases in a sample of Chilean institutionalized versus non-institutionalized elderly. - Carla P. Lozano; Cristian Vergara; Ximena Mulan Mercedes Lee (Universidad de Concepción., 2018)
Chile is experiencing a process of demographic aging with an increase in the number of elderly people, a percentage of which resides in Long-term Establishments for the Elderly (LEE). However, there is little information on the reality of the elderly in these long-term care facilities, so this study was conducted to compare the epidemiological profile of the prevalent oral pathologies as well as chronic non-communicable diseases (NCDs), of institutionalized versus non-institutionalized elderly subjects. Seventy-six institutionalized and forty-three non-institutionalized subjects were examined intraorally, and their clinical health record, gender and age were obtained, according to inclusion/exclusion criteria. The results indicate that female gender is the most common, with an average age of 78.5 year, with those 80 years old and above comprising the predominant group. The most prevalent oral lesions within the institutionalized group were denture stomatitis and irritative hyperplasia, while in the non-institutionalized these two lesions were found less frequently. As for the presence of xerostomia, there was no difference between the groups. The most common condition in both groups was total maxillary and mandibular edentulous, with the latter variable present more frequently in the institutionalized group (p<0.05). The predominant NCD for both groups were arterial hypertension, arthritis-osteoarthritis and diabetes mellitus (p>0.05), and depression was the most prevalent NCD in the non-institutionalized group (p<0.05). This study provides valuable information on the epidemiology of elderly´s oral lesions and NCDs to inform the decision-making process of public health policies